Focus of attention and verbal instructions: Strategies of elite track and field coaches and athletes - Porter, J. M.; Wu, W. F.; Partridge, J. A. (Sport Science Review, 2010)
It is well documented that directing attention externally enhances motor skill learning and performance under controlled experimental conditions. What is not well understood is how verbal instructions (VI) and feedback provided by coaches in authentic environments influences athletes' focus of attention. Thus, the purpose of this study was to investigate the type of VI and feedback provided by experienced coaches during practice, and how this information influenced elite athletes' focus of attention during competition. Participants were athletes competing at the USA Track and Field Outdoor National Championships. Participants completed a survey inquiring about the VI and feedback provided during practice and what they focused on while competing. The data revealed that 84.6% of the participants reported that coaches provided instructions during practice that promoted an internal focus of attention. Participants also reported they utilize internal focus cues 69% of the time during competition. These results suggest that this sample of coaches provided instructions that focused athletes' attention internally. This practice strategy is inconsistent with motor learning research, which shows learning and performance are enhanced when using an external focus of attention during motor skill execution. Recommendations are made to improve coaching education curriculums, bridging the gap between science and application.